Regulation of Cell Proliferation Using Tissue Engineering in MIN6 Cells - Naoko Kinoshita (Cell Transplantation, 2001)
Pancreatic islet transplantation for patients with diabetes mellitus has been hindered by the problem of donor shortage, as is the case for transplantation of other organs. Among several measures to overcome this problem, cell transplantation using xenogenic cell lines has been considered. For the treatment of diabetic patients, a murine pancreatic β-cell line MIN6 is a potential source of cell transplant. In order to restrict otherwise unlimited proliferation of transplanted MIN6 cells, cells are rendered to form spheroidal aggregates (SMIN6) on nonadherent culture dishes. SMIN6 stopped its growth around day 7 with a diameter of 220 ± 40 μm and kept its size almost constant at least until day 28. SMIN6 cells, however, had reduced responsiveness of insulin secretion to glucose concentration compared with MIN6 cells cultured in a monolayer. On the other hand, spheroid MIN6 cells formed in the presence of extracellular matrix gel (SMIN6E) possessed the capacity for glucose-dependent insulin secretion comparable with conventional MIN6 cells. SMIN6E encapsulated in agarose beads (SMIN6E-B) was also viable for at least 1 month in vitro with a constant diameter and favorable glucose responsiveness. The development of spheroid-type MIN6 may contribute to the future clinical application of MIN6 or other β-cell lines for treatment of diabetes mellitus.